1996
DOI: 10.1103/physrevb.54.12361
|View full text |Cite
|
Sign up to set email alerts
|

Critical properties of two-dimensional Josephson-junction arrays with zero-point quantum fluctuations

Abstract: We present results from an extensive analytic and numerical study of a twodimensional model of a square array of ultrasmall Josephson junctions. We include the ultrasmall self and mutual capacitances of the junctions, for the same parameter ranges as those produced in the experiments. The model Hamiltonian studied includes the Josephson, E J , as well as the charging, E C , energies between superconducting islands. The corresponding quantum partition function is expressed in different calculationally convenien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 54 publications
4
48
2
Order By: Relevance
“…This simplification cannot be used for the integer fields, except when C m = 0, in which case the m(τ, r) fields can be summed up exactly. This approach allows to build up look up tables that introduce an adequate effective potential [15].…”
Section: A Parameter Values In the Simulationsmentioning
confidence: 99%
“…This simplification cannot be used for the integer fields, except when C m = 0, in which case the m(τ, r) fields can be summed up exactly. This approach allows to build up look up tables that introduce an adequate effective potential [15].…”
Section: A Parameter Values In the Simulationsmentioning
confidence: 99%
“…The effects of external magnetic fields on phase transitions have been studied both in the classical arrays without charging energy [1] and in the quantum arrays [9][10][11][12]. However, most existing analytical works on the latter have employed mean-field-like approximations, which are not reliable in two dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…In the opposite limit, on the other hand, it is well known that there exists an interesting duality between charges and vortices [3,4], and the system with only junction capacitance at zero temperature undergoes a chargeunbinding Berezinskii-Kosterlitz-Thouless (BKT) transition [5] from the insulating phase to the superconducting one as the ratio E J /E 1 with E 1 ≡ e 2 /2C 1 is increased. The critical value (E J /E 1 ) c , beyond which the array is superconducting, has been found 0.6 in experiment [6], 0.23 in the duality argument [4] and in the variational method [7], 0.51 in perturbation expansion [8], and 0.36 in quantum Monte Carlo simulations [9]. As C 0 is increased from zero in this system, the interactions between charges are screened, with the screening length given by Λ ≡ C 1 /C 0 [4], and the nature of the phase transition is expected to alter.…”
Section: Introductionmentioning
confidence: 99%
“…A reentrance of the phase stiffness was already found for a related model in Ref. [10], but the authors concluded that the drop of the helicity modulus at lowest temperatures was probably due to the finiteness of the Trotter number P . Systematic extrapolations in the Trotter number and in the lattice size have been done, and presented in Figs.…”
Section: Resultsmentioning
confidence: 90%
“…[10], by derivation of the path-integral expression of the partition function (see Appendix). Kosterlitz's renormalization group equations provide the critical scaling law for the finite-size helicity modulus Υ L :…”
Section: Numerical Simulationsmentioning
confidence: 99%